MAGNETIC PROPERTIES OF THE TWO-LEG ZIG-ZAG LADDER IN QUANTUM SPIN SYSTEM NH4CuCl3 - Teguh Yoga Raksa; Budhy Kurniawan (Jurnal Sains Materi Indonesia, 2002)
MAGNETIC PROPERTIES OF THE TWO-LEG ZIG-ZAG LADDER IN QUANTUM SPIN SYSTEM NH4CuCl3. Numerical analysis of the two-leg zig-zag ladder as a single chain with next-nearest neighbour interactions has been formulated by Cabra (1999) with the following Hamiltonian: Other formulation for two leg zig-zag ladder with dimmerized chains and coupling between the chains is as follow : From these formulations, we study the closing of the gap at zero magnetization by means of the fine—tuning mechanism and disappreance of the 1/2 plateau (gap) at ﬁnite by alternating dimerization of the chains along the rungs. We also described NH4CuCl3 under high magnetic ﬁelds in a two-leg system.